Beyond the Whiteness: Environmental Concerns in the Visual Narratives of Carrara Marble Quarries - Quagliati, Noemi (2022)
Marble extraction in the Italian Apuan Alps has been known since Roman times, and its historical importance is symbolized by masterpieces of Western art history. However, the Carrara marble industry has recently received harsh criticism for operating in the protected area of the Apuan Alps Regional Park, recognized by UNESCO since 2015. Environmental and social concerns about mining have arisen from the extreme acceleration of all the productive phases of the extractive industry. From the mid-twentieth century, the exploitation of geological deposits of marble grew exponentially thanks to the development of powerful extraction technologies and a global export economy that creates only relatively few occupations in Carrara. Within this context, photographic and cinematographic projects have increasingly focused on the environmental risks created by the marble mining industry. This article shows how visual representations of Carrara have changed in recent years via an analysis of three case studies: the internationally acclaimed documentary Anthropocene: The Human Epoch (2018), the climbing project and Italian short film Carie (Cavity 2019), and Lorenzo Shoubridge’s naturalistic photographs in Apuane: terre selvagge (Apuan Wildlands 2018). These case studies offer an innovative perspective on the landscapes of marble extraction. Previously, these landscapes were represented following other visual trends emphasizing the technological sublime found in the geometric shapes of the white quarries, the working conditions of marble laborers, and the myth of the purity of marble used in artistic sculptures. The three examples analyzed in this paper attempt to go ‘beyond the whiteness’ by focusing on the scale of environmental destruction (Anthropocene: The Human Epoch), the more-thanhuman perspective (Apuane terre selvagge), and the social struggle for preserving a mountain region through creative solutions (Carie). In other words, new aesthetic and ethical sensibilities are challenging established twentieth-century narratives of the Carrara marble quarries by focusing on a new element: the environment. Cover image: Saverio Salvioni, Cava di Ravaccione, 1810–1813 (Source: Archivio di Stato Massa e Pontremoli)